Religion and Public Life in the Pacific Northwest: The None Zone - Killen, Patricia O'Connell; Silk, Mark (Rowman & Littlefield Publishers, 2004)
When asked their religious identification, more people answer 'none' in the Pacific Northwest than in any other region of the United States. But this does not mean that the region's religious institutions are without power or that Northwesterners who do attend no place of worship are without spiritual commitments. With no dominant denomination, Evangelicals, Mainline Protestants, Catholics, Jews, adherents of Pacific Rim religious traditions, indigenous groups, spiritual environmentalists, and secularists must vie or sometimes must cooperate with each other to address the regions' pressing economic, environmental, and social issues. One cannot understand this complex region without understanding the fluid religious commitments of its inhabitants. And one cannot understand religion in Oregon, Washington, and Alaska without Religion and Public Life in the Pacific Northwest.